2022
DOI: 10.1021/acsaem.1c03050
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made Amino-Based Self-Assembled Monolayers Grafted on Electron Transport ZnO Layers: Perovskite Solar Cell Performance and Modified Interface Relationship

Abstract: Self-assembled monolayers (SAMs) have been grafted via a carboxylic acid group onto a ZnO electron transport layer to control the growth and structure of a hybrid perovskite CH 3 NH 3 PbI 3 (MAPI) used as an active layer in a solar cell. In addition to the basic molecule, HO 2 C−PP−NH 2 (PP = biphenyl), two bipolar molecules, HO 2 C− (CH 2 ) n −PP−CH 2 −NH 3 Cl (A: n = 0), 4′-(carboxy)-(1,1′-biphenyl)-4aminomethyl hydrochloride and B: (n = 1), 4′-(carboxymethyl)-(1,1′biphenyl)-4-aminomethyl hydrochloride, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Regarding the key issue of passivation and stability improvement in perovskite cells, some studies have also shown the successful use of push-pull SAMs. For instance, biphenyl-based SAMs have been successfully used recently as an interfacial layer between the ZnO electron transport layer and CH3NH3PbI3 hybrid perovskite to improve their stability [110], as shown in Figure 10. Still within the use of push-pull chromophores as interfacial layers, the push-pull nature has also been exploited with layer deposition on top of metal oxides to improve electron injection from the photoactive absorber to the metal oxide, resulting in the enhancement of the device's photocurrent.…”
Section: Sams Of Push-pull Chromophores To Improve Perovskite Solar C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the key issue of passivation and stability improvement in perovskite cells, some studies have also shown the successful use of push-pull SAMs. For instance, biphenyl-based SAMs have been successfully used recently as an interfacial layer between the ZnO electron transport layer and CH3NH3PbI3 hybrid perovskite to improve their stability [110], as shown in Figure 10. Still within the use of push-pull chromophores as interfacial layers, the push-pull nature has also been exploited with layer deposition on top of metal oxides to improve electron injection from the photoactive absorber to the metal oxide, resulting in the enhancement of the device's photocurrent.…”
Section: Sams Of Push-pull Chromophores To Improve Perovskite Solar C...mentioning
confidence: 99%
“…Regarding the key issue of passivation and stability improvement in perovskite cells, some studies have also shown the successful use of push-pull SAMs. For instance, bi-phenylbased SAMs have been successfully used recently as an interfacial layer between the ZnO electron transport layer and CH 3 NH 3 PbI 3 hybrid perovskite to improve their stability [110], as shown in Figure 10.…”
Section: Sams Of Push-pull Chromophores To Improve Perovskite Solar C...mentioning
confidence: 99%
“…At the same time, the V OC and PCE values of the creatine-added device increased compared to the untreated device, and the stability was also improved. Kouki et al (2022) synthesized a new molecule, HOOC−(CH 2 ) n −PP−(CH2) n NH 3 + Cl − , and grafted it onto ZnO layer as SAM, making the crystallinity of perovskite better and the stability of the device stronger.…”
Section: Biological Materialsmentioning
confidence: 99%
“…This issue can be overcome by enhancing the photodetection performance with heterojunction combinations. , Fortunately, these heterostructures, most of the time, allow the formation of self-powered photodetection abilities that can show a photoresponse with no external bias, although the typical ZnO PDs require a bias voltage for the separation of the photogenerated charge carriers. Emerging photovoltaic technologies, especially those based on solution-processed thin films, are very promising to be integrated into self-powered photodetectors. , The use of perovskite, a member of the emerging photovoltaic family, has increased in recent years in light of developments in semiconductor technologies. , All-inorganic cesium halide perovskites (IHPs) having the CsPbX 3 (X = Br, Cl, and I) formula have been widely employed as light-absorbing materials for optoelectronic devices owing to their favorable features such as high optical absorption, large carrier mobility, and ease of synthesis methods . Additionally, numerous research works indicate that ZnO is a preferable electron transport layer (ETL) material for CsPbX 3 in solar cell applications. , In recent studies, heterostructures or composites prepared from ZnO/CsPbBr 3 have exhibited outstanding photodetection performances. However, most of the research consists of either ZnO thin films or 1D ZnO nanostructures as heterostructure components. As proved by our previous research, 3D ZnO in NF or NS morphologies is superior to 1D ZnO in terms of the light absorption ability and PEC performances .…”
Section: Introductionmentioning
confidence: 99%
“…28 Additionally, numerous research works indicate that ZnO is a preferable electron transport layer (ETL) material for CsPbX 3 in solar cell applications. 29,30 In recent studies, heterostructures or composites prepared from ZnO/CsPbBr 3 have exhibited outstanding photodetection performances. 31−34 However, most of the research consists of either ZnO thin films or 1D ZnO nanostructures as heterostructure components.…”
Section: Introductionmentioning
confidence: 99%